Kebijakan Hukum Pidana tentang Pengenaan Bersamaan Rehabilitasi dan Pidana Pokok terhadap Pelaku Tindak Pidana Narkotika Perspektif Keadilan - Dediansyah Dediansyah; Syamsuddin Syamsuddin; Musmuliadin Musmuliadin; Ridwan Ridwan (Bulletin of Community Engagement, 2026)
Narcotics abuse in Indonesia is a multidimensional issue that involves not only criminal justice concerns but also public health challenges. In law enforcement practice, narcotics addicts and abusers are frequently sentenced to imprisonment without adequate consideration of their need for rehabilitation, raising questions regarding justice and the effectiveness of criminal sanctions. This study aims to analyze criminal law policies concerning the simultaneous imposition of rehabilitation measures and principal criminal penalties on narcotics offenders and to evaluate such policies from a justice perspective. The research employs a normative legal method using statutory and conceptual approaches. The data consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively through a literature-based study. The findings indicate that the Indonesian legal system, through Law Number 35 of 2009 on Narcotics and Law Number 1 of 2023 concerning the Criminal Code, provides a normative basis for the implementation of the double track system, which combines criminal punishment with rehabilitative measures. However, the implementation of this policy remains suboptimal due to differing perceptions among law enforcement officials, limitations in integrated assessment mechanisms, and inadequate rehabilitation facilities. From a justice perspective, the simultaneous imposition of principal penalties and rehabilitation can be viewed as a compromise between retributive, utilitarian, and restorative justice, aiming to balance punishment with offender recovery. Therefore, its application should be carried out proportionally and differentially based on the category of offender, degree of culpability, and level of dependency. Such an approach is expected to promote substantive justice, enhance the effectiveness of narcotics control, and provide more humane protection for society.